2016
DOI: 10.1681/asn.2015010095
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor 3–Deficient Dendritic Cells Modulate Splenic Responses to Ischemia-Reperfusion Injury

Abstract: The plasticity of dendritic cells (DCs) permits phenotypic modulation ex vivo by gene expression or pharmacologic agents, and these modified DCs can exert therapeutic immunosuppressive effects in vivo through direct interactions with T cells, either inducing T regulatory cells (T REG s) or causing anergy. Sphingosine 1-phosphate (S1P) is a sphingolipid and the natural ligand for five G protein-coupled receptors (S1P1, S1P2, S1P3, S1P4, and S1P5), and S1PR agonists reduce kidney ischemia-reperfusion injury (IRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 65 publications
7
39
0
Order By: Relevance
“…Another possibility is that regulatory DC could inhibit innate mediated inflammatory responses through other mechanisms. For example, in a similar murine model of renal IRI, 0.5 × 10 6 regulatory BMDC, generated by pretreatment with an A2aR agonist, suppressed the innate inflammatory response by altering the function of effector cells through mechanism that did not increase Tregs (17). Data in our studies would indicate that the infused IgM/LPS pretreated regulatory BMDC instruct the host regulatory mechanisms via production of anti-inflammatory cytokines (e.g IL10) and the PD1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that regulatory DC could inhibit innate mediated inflammatory responses through other mechanisms. For example, in a similar murine model of renal IRI, 0.5 × 10 6 regulatory BMDC, generated by pretreatment with an A2aR agonist, suppressed the innate inflammatory response by altering the function of effector cells through mechanism that did not increase Tregs (17). Data in our studies would indicate that the infused IgM/LPS pretreated regulatory BMDC instruct the host regulatory mechanisms via production of anti-inflammatory cytokines (e.g IL10) and the PD1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates isolated from BMDC pretreated with IgM and LPS (400ng/ml) at 37°C for 1 hr were subjected to Western blotting using previously published techniques (17). Tubulin was detected with mouse anti-β-tubulin (clone 3F3-G2, Santa Cruz Biotechnology, Dallas, TX) and a secondary IRDye 800CW labelled goat anti-mouse (LI-COR Biosciences, Lincoln,NE).…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α, chemokine (C-C motif) ligand 2, and C-X-C motif chemokine 10) by renal cells. A recent study by Bajwa et al [73] has also shown that bone marrow-derived dendritic cells deficient in sphingosine 1-phosphate receptor 3 can prevent ischemia-repufusion-induced AKI via a spleen-dependent mechanism and splenic T-regulatory cell expansion. These experimental results are in line with a recent clinical study showing inflammatory cytokine (IL-8), which augments the prediction of kidney recovery and mortality in AKI patients on renal replacement therapy [74] .…”
Section: Immune Responsementioning
confidence: 97%
“…Immature DCs secrete higher level of IL-10 than do mature DCs, and IL-10 produced by DCs induces immune suppression by modulating CD4 + T cells [52]. Injection of immature DCs reduced renal IRI by generating more Tregs [53]. Other studies have indicated that the protective effect of immature DCs on the kidney is partly attributed to IL-10-mediated activation of Tregs [54].…”
Section: Discussionmentioning
confidence: 99%